Association Between Polymorphisms in the 5′ Region of the GALR1 Gene and Schizophrenia in the Northern Chinese Han Population: A Case–Control Study - Li Y (Dove Medical Press, 2020)
Ya Li, Meng Gao, Kuo Zeng, Jia-xin Xing, Feng-ling Xu, Jin-feng Xuan, Xi Xia, Yong-ping Liu, Jun Yao, Bao-jie Wang School of Forensic Medicine, China Medical University, Shenyang 110122, People’s Republic of ChinaCorrespondence: Bao-jie Wang; Jun Yao Email wangbj77@163.com; yaojun198717@163.comBackground: Epidemiological studies have shown that genetic factors are among the causes of schizophrenia. Galanin receptor 1 is an inhibitory receptor of galanin that is widely distributed in the central nervous system. This study mainly explored the relationship between polymorphisms of the 5′ region of the GALR1 gene and schizophrenia in the northern Chinese Han population.Methods: A 1545 bp fragment of the 5′ regulatory region of the GALR1 gene was amplified and sequenced in 289 schizophrenia patients and 347 healthy controls.Results: Among the haplotypes composed of the 16 detected SNPs, the haplotype H3 was identified as conferring a risk of schizophrenia (p=0.011, OR=1.430, 95% CI=1.084– 1.886). In addition, the haplotypes H4 and H7 were both protective against schizophrenia (p=0.024, OR=0.526, 95% CI=0.298– 0.927; p=0.037, OR=0.197, 95% CI=0.044– 0.885, respectively). In the subgroup analysis by sex, it was found that seven SNP alleles (rs72978691, rs11662010, rs11151014, rs11151015, rs13306374, rs5373, rs13306375) conferred a risk of schizophrenia in females (p< 0.05), while allele G of rs7242919 (p=0.007) was protective against schizophrenia in females. Moreover, the rs72978691 AA+AC genotype (p=0.006, OR=1.874, 95% CI=1.196– 2.937, power=0.780), rs7242919 CC+CG genotype (p=0.002, OR=2.027, 95% CI=1.292– 3.180, power=0.861), rs11151014 GG+GT genotype (p=0.008, OR=1.834, 95% CI=1.168– 2.879, power=0.735), rs11151015 GG+AG genotype (p=0.002, OR=2.013, 95% CI =1.291– 3.137, power=0.843), rs13306374 CC+AC genotype (p=0.006, OR=1.881, 95% CI=1.198– 2.953, power=0.788), and rs13306375 GG+AG genotype (p=0.006, OR=1.868, 95% CI=1.194– 2.921, power=0.770) increased the risk of schizophrenia in females. The haplotype FH2 consisting of rs72978691, rs11662010, rs7242919, rs11151014, rs11151015, rs13306374, rs5373, and rs13306375 may also be associated with the risk of schizophrenia in females (p=0.024).Conclusion: This study identified an association between polymorphisms in the 5′ region of the GALR1 gene and schizophrenia, especially in females.Keywords: galanin receptor 1, schizophrenia, single-nucleotide variant, genetic polymorphism, northern Chinese Han population